Concurrent-Validity and Reliability of Photocells in Sport: A Systematic Review - Multhuaptff, Weilhelmn (2024)
Specific physical qualities such as sprint running, change-of-direction or jump height are determinants of sports performance. Photocell systems are practical and easy to use systems to assess the time from point A to point B. In addition, these photoelectric systems are also used to obtain the time of vertically displaced movements. Knowing the accuracy and precision of photocell timing can be a determinant of ensuring a higher quality interpretation of results and of selecting the most appropriate devices for specific objectives. This systematic review aimed to identify and summarize studies that have examined the validity and reliability of photocells in sport sciences. A systematic review of PubMed, SPORTDiscus, and Web of Science databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. From the 164 studies initially identified, 16 were fully reviewed, and their outcome measures were extracted and analyzed. Photocells appear to have a strong agreement with force plates (gold standard), but are not interchangeable to measure the vertical jump. For monitoring horizontal displacement, double beam systems, compared to single beam systems, are more valid and reliable when it comes to avoiding false triggers caused by swinging arms or legs.